PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016 DAN 2017 - Amarakamini, Ni Putu; Suryani, Elly (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
Financial statements are prepared to give information about the condition of a company and are an important communication tool between management and stakeholders. Fraud especially, over financial statements occurs because of the motivation and encouragement of various parties, both from within and outside the company. The occurrence of fraud also arises because of a conflict of interest between the agent and the principal. The Association of Certified Fraud Examiners (ACFE) said that the manufacturing industry is ranked second as the most frequent fraud in the world. This study aims to determine fraud pentagon factors (pressure, opportunity, rationalization, ability, and arrogance) and fraudulent financial statements. This study also aims to investigate the influence of the fraud pentagon on fraudulent financial statements in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016 and 2017. This study uses secondary data from the annual report of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016 and 2017. The number of samples used was 102 companies and data processing was carried out using Eviews version 10. Based on the test results, fraud pentagon simultaneously has a significant effect on fraudulent financial statements. Partially it can be concluded that rationalization has a positive effect on fraudulent financial statements and opportunity has a significant negative effect on the fraudulent financial statement. While the variables of pressure, capability, and arrogance do not affect the fraudulent financial statement.